Ziarah: islamic tourism in Malaysia / Muhammad Salahuddin Shaharuddin - Shaharuddin, Muhammad Salahuddin (2018)
Malaysia as an Islamic country is promoting tourism worldwide so as to attract more tourists to visit Malaysia. Islamic tourism is associated with the religious, spiritual and cultural aspects of tourism. Malaysia is a peaceful and harmonious country of various races and religions. There are also a lot of attractive destinations that are situated in every state in Malaysia. The Government Initiative and also the services provided by the travel agencies has been meets with the Muslims demand in having Ziarah. This paper is investigating the various features and popular destinations of Islamic tourism as practiced in Malaysia. Using a qualitative approach, the data was collected from books, journals, magazines, websites and documents. This paper will contribute towards a better understanding about Islamic tourism and Malaysia destinations for tourist.